2020
DOI: 10.1016/j.clinre.2020.03.013
|View full text |Cite
|
Sign up to set email alerts
|

A case of COVID-19 patient with the diarrhea as initial symptom and literature review

Abstract: KEYWORDS Diarrhea; Novel coronavirusSummary Since Dec 2019, a cluster of pneumonia outbreak in Wuhan, Hubei province, China, and soon spread to all province of China. The pathogen was proved to be a novel betacoronavirus called 2019 novel coronavirus (officially named by the World Health Organization as COVID-19). The typical clinical manifestations were fever, cough, dyspnea, and myalgia or fatigue. Less common symptoms included headache, diarrhea, nausea and vomiting. However diarrhea as the first symptom is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 15 publications
1
24
0
4
Order By: Relevance
“…13,14 Our findings may contribute to understanding of Covid-19 transmission and the importance of GI disorders as one of the primary symptoms of the disease. 11,[13][14][15] The case fatality rate in this series was 41.7%, as had been reported in critically patients in Seattle and China 9,16 . The age of dead patients was significantly higher than that of the survivors, with a mean of 59.4 years being 62.5% male and with some comorbidity in 52.1% of the cases.…”
Section: Discussionsupporting
confidence: 79%
“…13,14 Our findings may contribute to understanding of Covid-19 transmission and the importance of GI disorders as one of the primary symptoms of the disease. 11,[13][14][15] The case fatality rate in this series was 41.7%, as had been reported in critically patients in Seattle and China 9,16 . The age of dead patients was significantly higher than that of the survivors, with a mean of 59.4 years being 62.5% male and with some comorbidity in 52.1% of the cases.…”
Section: Discussionsupporting
confidence: 79%
“…Diarrhea is the most common GI symptom reported and may be considered as an initial symptom in some infected patients ( D'Amico, Baumgart, Danese, & Peyrin-Biroulet, 2020 ; Yang, Zhao, et al, 2020 ). In comparison with adults in whom decreased appetite is prominent, vomiting is more prominent in children.…”
Section: Discussionmentioning
confidence: 99%
“…Three case reports included hematochezia as a symptom [17][18][19]. There are also several case reports that describe patients that present with only GI symptoms initially or throughout the course of their entire infection [20][21][22][23][24]. The largest study, a single-center study by Luo et al found that of 1141 confirmed cases of COVID-19, 16% presented with only GI symptoms [25].…”
Section: Incidental Covid-19 Findings Based On Abdominal Computed Tommentioning
confidence: 99%